The establishment of a digital seismic acquisition system and its subsequent application in the field. - Evans, Brian J. (Curtin University, 1984)
The seismic method in exploration geophysics consists of creating a mechanical disturbance at or close to the surface of the earth, and observing its effects at a number of chosen locations along the surface. The purpose of seismic data acquisition is to record these effects in such a manner that their relation with the initial disturbance can be interpreted as a guide to the earth's subsurface structure (Nettleton, 1940).The validity of data interpretation depends upon the fidelity of recording. A better seismic interpretation can result from correctly collected data using instrumentation which faithfully records the seismic signal. Subsequent computer processing cannot reconstruct information which is not contained in the recorded field data. Hence, the quality of field data recording must be at an optimum level, otherwise the result will be an inferior interpretation (Donnell,1957).A reflection seismic data acquisition system was assembled and put into operation. The basic instrument was a Texas Instruments DFS IV, obtained from marine vessel M/V Banksia, and commissioned for land application.The system was tested and evaluated. The instrument analog filter phase distortion was studied in detail. The study indicated that phase distortion can be a major cause of seismic misties. Without a knowledge of the particular recording instrumentation filter transfer function, data processing bureaux may not compensate for phase distortion effects adequately (Gray et al., 1968).Once testing was completed satisfactorily, the operational system was applied to several practical field situations of commercial standard. A series of noise studies was performed to evaluate not only source generated noise, but also to study the effect of different types of energy sources on seismic data. In addition, two multi-fold seismic lines wore recorded, both of which were considered superior to those previously produced by the industry, at each location (Jacia, pers. comm., 1984).Finally, a single fold three-dimensional areal seismic survey was performed over the Woodada gas field. The results of this survey will be released after processing has been completed by Allied Geophysical Laboratories (University of Houston), and are not contained in this thesis.Future areas for field application are discussed. Recommendations are made for further research work in the area of phase distortion; the examination of different energy sources; a review of receiver properties and horizontally travelling seismic waves; a bore-hole seismic study and finally, a fourth-dimensional recording technique involving the performance of an offset VSP survey at the same time as an areal 3-D seismic survey.Volume 1 describes the establishment of the acquisition system and its subsequent field application.Volume 2 contains the Appendix of instrument tests and their analysis.